Formulation and development of soy okara cookies by blending with different levels of black scented rice flour: Formulation and development of soy okara cookies by blending with different levels of black scented rice flour - L SOPHIA DEVI; NILIMA KARAM; T SUNANDA DEVI; H NANITA DEVI (Journal of Oilseeds Research, 2020)
Protein malnutrition is widely recognized as a major health problem. Cookies are widely consumed and generally, they are rich in carbohydrates, fats and calories, but low in fibre, vitamins and minerals. Okara, the pulpy by-product generated during the manufacturing process of soymilk and tofu, is considered as a waste product and is either disposed off. A possible use for okara is in baked foods as it has a large amount of fibre and protein. Composite flour was prepared by substituting the wheat flour in the ratio of 10:10:80, 15:10:75, 20:10:70, 25:10:65 and 0:0:100 (control) of okara: black rice flour: wheat flour. The objective of the present study was to prepare nutritious cookies and to study the effect of different combination of okara powder on the nutritional and sensory quality of the developed cookies. In nutrient estimation of cookies, protein content increased from 5.15 % to 7.85 % with increased addition of okara powder. Treatment T4 gave the highest protein content (7.85%) as compared with the control sample T5 (3.26%). The overall acceptability scores for treatment T1, T2, T3 and T4 remains the same. So fortification of cookies can be done by replacing wheat flour with okara powder upto 10-25% without adversely affecting the sensory parameters.